Multidrug-resistant livestock-associated ST9-MRSA causing severe human infection without animal exposure: the food chain as a potential transmission route in China - Wei Zhang; Zi-hao Wu; Guo-feng Xing; Xuan Hou; Hui Wang; Yan-jiong Chen (Archives of Microbiology, 2026)

Inhibition of RBM25 preserves cardiac mitochondrial homeostasis and attenuates ischemic heart failure - Shu Liu; Hong Ding; Kejuan Li; Xiaowei Zhang (Journal of Molecular Histology, 2026)

Population structure analysis and construction of DNA fingerprinting in eggplant (Solanum melongena L.) based on whole-genome resequencing - Ruining Lai; Chuan Zhong; Jiechun Peng; Kongxiu Su; Duoduo Xiao; Bingying Zou; Meimei Shi; Jingjing Huang; Huarong Fang; Jinling He; Xinyuan Chen; Junwei Zhang; et al. (Genetic Resources and Crop Evolution, 2026)

Arbuscular mycorrhizal fungi recruit siderophore-producing phosphate solubilizing bacteria to mobilize sparingly soluble inorganic phosphate in subtropical orchard soils - Fengwa Zhu; Wei Zhang; Yongqiang Qin; Zengwei Feng; Yang Zhou; Xiaodi Liu; Qiutong Ling; Mingrong Deng; Honghui Zhu; Qing Yao (Applied Soil Ecology, 2026)

Photorhabdus metabolites reshape soil microbial communities and promote plant growth and insect resistance - Jaspher Ewany; Ivan Hiltpold; Emmanuel Defossez; Gaétan Glauser; Carla C.M. Arce; Wei Zhang; Sergio Rasmann; Ted C.J. Turlings; Ricardo A.R. Machado (Applied Soil Ecology, 2026)

Long-term co-contamination with arsenic and PAHs reshapes soil microbial interactions and functional allocation - Meng Zhou; Yanfei Wei; Wei Zhang; Chi Zhang; Xiangwu Yao; Baolan Hu (Applied Soil Ecology, 2026)

Genome-wide linkage and association mapping identified a novel candidate gene, TaGLK-A1, underlying fructan content in wheat grain - Zhankui Zeng; Yue Zhao; Junge Bi; Qunxiang Yan; Wei Zhang; Feng Chen; Chunping Wang (Theoretical and Applied Genetics, 2026)
Key message A nuclear-localized G2-like transcription factor, TaGLK-A1 ( TraesCS7A02G539600 ), was identified as a strong candidate gene for grain fructan content in wheat using GWAS, linkage mapping and transcriptome analysis. Abstract Fructans, a type of natural polysaccharides or oligosaccharides polymerized from fructose molecules, play important physiological roles in crops and confer great health benefits to humans. In this study, we detected 78 stable loci associated with fructan content across all 21 wheat chromosomes across three environments and in the BLUE, explaining 4.4–10.0% of the phenotypic variance by a genome-wide association study (GWAS) using 243 wheat cultivars and advanced lines genotyped with the Axiom wheat 660 K single-nucleotide polymorphism (SNP) array. Among these, a significant locus of fructan content was localized in a 4.02 Mb interval (713.87–717.89 Mb) on chromosome 7AL, designated QGfc.hkd-7A . QGfc.hkd-7A was validated in 164 recombinant inbred lines (RILs) from a cross between Avocet and Chilero in five environments using diversity array technology (DArT), which was tightly linked to DArT markers SNP2260399 , 3575400 , SNP3028492 , SNP100415949 , 3533474 and 100091413 , accounting for 16.4–24.6% of the total phenotypic variance in the RIL population. Favorable allele of QGfc.hkd-7A significantly increased grain fructan content by 10.5% ( P QGfc.hkd-7A , we generated differential gene expression profiles using RNA-seq for high-fructan (AC6012) and low-fructan (AC6361) lines from the Avocet/Chilero population. TaGLK-A1 ( TraesCS7A02G539600 ), a differential expressed gene (DEG), was subsequently cloned and sequenced from both genotypes. Sequence comparison of the full-length TaGLK-A1 cDNA (1545 bp) revealed a single SNP at position 109 causing a proline (CCA) to threonine substitution between Avocet and Chilero. Subcellular localization analysis confirmed that the G2-like transcription factor encoded by TaGLK-A1 localizes to the nucleus. Transactivation assays revealed that it lacks intrinsic transcriptional activation activity, suggesting it may function as a transcriptional repressor or require cofactors for regulatory function. These results provide a novel and strong candidate gene for fructan content and a forward genetics strategy for gene discovery in molecular breeding.

Formation Mechanism of Meter-Scale Large Deformation in Hard Rock with Sillimanite–Plagioclase–Biotite Schist Bands in a Deep TBM Tunnel - Zhibin Yao; Lianjie Fu; Yongrun Xiong; Chengxiang Yang; Fengpeng Zhang; Fuqi Kang; Song Chen; Wei Zhang; Lei Hu (Rock Mechanics and Rock Engineering, 2026)

Evaluation of the substrate profile of microbial-host-isozyme reveals the role of BvDPP4 in inflammatory bowel disease - Yingying Zhuo; Sen Yan; Zhiwei Zhang; Bangjian Dong; Dandan Yin; Yongping Wen; Yuejian Mao; Zhipeng Zhang; Kai Wang; Changtao Jiang (Science China Life Sciences, 2026)

Integrating slush samples and eDNA metabarcoding to enhance marine fish biodiversity monitoring - Qilin Gutang; Hancheng Zhao; Xiaoxuan Yu; Yan Gao; Kunhuan Li; Jianghua Yang; Xiaowei Zhang; Ping Li; Edmond Sanganyado; Zonghang Zhang; Jianqing Lin; Wenhua Liu (Fisheries Research, 2026)

Fungal-driven carbon sequestration within soil aggregates under paddy multicropping - Wei Zhang; Wen Liu; Leyan Zhang; Mengyao Zhou; Rui Xiong; Hongling Qin; Anlei Chen; Baoli Zhu; Zhiqiang Fu; Pan Long (Applied Soil Ecology, 2026)

Genus-level microorganisms as the optimal taxonomic level for assessing microbial health in paddy soil: A microbial relative abundance-fertility functions synergy analysis - Yinan Xu; Jing Sheng; Jianwei Zhang; Zhi Guo; Hongjiang Liu (Applied Soil Ecology, 2026)

Cross-domain microbial interactions mediate soil multifunctionality during crop growth stages - Guo Chen; Chao Chang; Zihan Yan; Hao Wang; Qingwei Zhang; Jian Wang; Ming Li; Wei Zheng; Ding He; Biao Zhu (Applied Soil Ecology, 2026)

Semi-analytical solution for two-dimensional transient groundwater flow associated with dewatering of excavations involving a suspended waterproof curtain and river - Jiangwei Zhang; Yue Fan; Yue Ma; Xiuyu Liang (Advances in Water Resources, 2026)

Optimization of nitrogen-soil microbial interactions to regulate carbon and nitrogen footprints and enhance yield sustainability in maize fields - Tiantian Meng; Jingjing Shi; Xiangqian Zhang; Xiaoyu Zhao; Xiaorong Wu; Meiren Rong; Yanan Liu; Xingxing Guo; Shuli Wei; Yongfeng Ren; Zhanyuan Lu; Jianwei Zhang (Applied Soil Ecology, 2026)

A trade-off between warming responses and ozone sensitivity in nodulating versus non-nodulating soybean rhizosphere nitrogen cycling - Enzhu Hu; Weiwei Zhang; Yating Li (Applied Soil Ecology, 2026)

The origin of loess microstructure: 3D insights from initial aeolian dust packing - Weiwei Zhang; Yanrong Li; Jianguo Zheng; Yongtang Yu; Xin Huang; Jianmin Zhu (Aeolian Research, 2026)

Co-exposure to decabromodiphenyl ethane and cadmium disrupts gut homeostasis in earthworms (Eisenia fetida): Insights from microbiome-metabolome analysis - Zhihua Qiao; Qitong Huang; Dongyang Li; Hongxia Zhang; Wei Zhang (Applied Soil Ecology, 2026)

Hydrothermal evolution of high-latitude frozen soil during freeze-thaw cycles - Jiao Huang; Xiabing Yue; Xueying Wang; Hongwei Zhang (Advances in Water Resources, 2025)

Compared with plant diversity and soil fungal diversity, soil bacterial diversity drives ecosystem multifunctionality during the vegetation restoration process - Hengkang Xu; Chao Chen; Zhuo Pang; Guofang Zhang; Weiwei Zhang; Haiming Kan (Applied Soil Ecology, 2025)

Metagenomic insights into the effects of desiccation on functions associated with biogeochemical cycles and resistome of microbial communities - Lin Chen; Qiaoling Zhang; Wei Zhang; Kangyun Zhu; Qingyu Xu; Kaiming Hu; Qiuyue Feng; Yuyan Liu; Binhao Wang (Applied Soil Ecology, 2025)

Towards distinguishing biotic and abiotic contributions to phenol oxidase activity: Current understanding and future perspective - Taiki Mori; Senhao Wang; Cong Wang; Wei Zhang; Jiangming Mo (Applied Soil Ecology, 2025)

Microbial keystone taxa and nitrogen cycling enzymes driven by the initial quality of litter jointly promoted the litter decomposition rates in the Tengger Desert, northern China - Guisen Yang; Lei Huang; Wei Zhang; Yafei Shi; Zhiying Ning; Rui Hu; Zhishan Zhang (Applied Soil Ecology, 2025)

The coupling effects of long-term straw return and plant selection facilitate rhizosphere nitrogen supply by promoting recruitment of core genera - Lei Xu; Yan Zhou; Congrong Miao; Jianwei Zhang; Yanfeng Ding; Zhenghui Liu; Weiwei Li; Yu Jiang; Ganghua Li (Applied Soil Ecology, 2025)

Higher temperatures decreased the abundance of arbuscular mycorrhizal fungi and the complexity of their networks by reducing tree diversity - Dan Xiao; Yixin Tang; Wei Zhang; Peilei Hu; Kelin Wang (Applied Soil Ecology, 2025)

Tibetan sheep grazing and selenium addition promote soil carbon and nitrogen mineralization in alpine meadow - Jianwei Zhang; Zhe Wu; Yang Liu; Fujiang Hou (Applied Soil Ecology, 2025)

Metagenomics reveals soil nitrogen cycling after vegetation restoration: Influence of different vegetation restoration strategies - Hengkang Xu; Chao Chen; Wenqing Chen; Zhuo Pang; Guofang Zhang; Weiwei Zhang; Haiming Kan (Applied Soil Ecology, 2024)

Nitrogen deposition in the middle-aged and mature coniferous forest: Impacts on soil microbial community structure and function - Jun Zhang; Fei Yu; Zhaoyong Hu; Shouqin Sun; Xiangyang Sun; Juying Sun; Wei Zhang; Genxu Wang (Applied Soil Ecology, 2024)

Gradual and abrupt increase in atmospheric CO2 concentrations trigger divergent responses of microbial necromass accumulation in paddy soils - Xueli Ding; Dongqiao Yang; Zhenghua Hu; Lidong Shen; Wei Zhang; Xuefeng Zhu; Josep Peñuelas; Zhurong Wu; Hao He; Hongbo He; Chao Liang (Applied Soil Ecology, 2024)

Effect of long-term nitrogen addition on the kinetics of phosphatases in a subtropical forest in southern China - Taiki Mori; Senhao Wang; Cong Wang; Wei Zhang; Jiangming Mo (Applied Soil Ecology, 2024)

Pore-scale investigation of solute dispersion behavior in porous media under a two-phase co-flow condition - Chunwei Zhang; Kai Zhang; Jiale Mo; Zijing Li; Tetsuya Suekane; Yuncong Wang; Ming Li (Advances in Water Resources, 2024)

Understanding aerosol–climate–ecosystem interactions and the implications for terrestrial carbon sink using the Community Earth System Model - Haiwei Zhang; Longhui Li; Jia Song; Zaeem Hassan Akhter; Jingjia Zhang (Agricultural and Forest Meteorology, 2023)

Virulence mechanisms of vibrios belonging to the Splendidus clade as aquaculture pathogens, from case studies and genome data - Weiwei Zhang; Chenghua Li (Reviews in Aquaculture, 2021)
The Vibrio genus belonging to the Splendidus clade includes 16 described species and can infect a broad host range of cultured animals in marine environments, resulting in various diseases and high mortality, thus leading to high economic losses in aquaculture. Here, we provide a brief description of the virulence of Splendidus clade pathogens and the known or potential virulence factors as well as the virulence regulation factors provided by both case studies and genome data. Splendidus clade pathogens possess virulence factors, including adhesins, extracellular proteases, haemolysins and siderophores, to adhere to, invade and combat hosts. Global regulators, such as the quorum sensing system and σ factors, are involved in virulence regulation. Chemotaxis, flagellum, secretion and toxin‐antitoxin systems, as well as small RNAs that are frequently involved in virulence, are also included in the discussion of the genome data of Splendidus clade pathogen. A better understanding of the pathogenesis, virulence factors and virulence regulation will not only illustrate the means used by Splendidus clade pathogens to infect their hosts but also offer new targets for the development of control strategies against Splendidus clade pathogen infection in aquaculture.